Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-40507-8
|View full text |Cite
|
Sign up to set email alerts
|

Phagosomal and mitochondrial alterations in RPE may contribute to KCNJ13 retinopathy

Abstract: Mutations in KCNJ13 are associated with two retinal disorders; Leber congenital amaurosis (LCA) and snowflake vitreoretinal degeneration (SVD). We examined the retina of kcnj13 mutant zebrafish ( obelix td15 , c.502T > C p.[Phe168Leu]) to provide new insights into the pathophysiology underlying these conditions. Detailed phenotyping of obelix td15 fish revealed a late onset retinal dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…The samples were embedded in Tissue-Tek O.C.T embedding medium (VWR, Radnor, PA, USA) using dry ice and 12 μm sections were collected onto Superfrost ® PLUS slides (VWR) using a Leica CM1850 cryostat. The RNAscope assay was performed using the RNAscope Fluorescent Multiplex Detection v2 kit (ACD) as previously described ( 52 ). The ush2a target probe and odc1 and dapB control probes were designed and provided by ACD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were embedded in Tissue-Tek O.C.T embedding medium (VWR, Radnor, PA, USA) using dry ice and 12 μm sections were collected onto Superfrost ® PLUS slides (VWR) using a Leica CM1850 cryostat. The RNAscope assay was performed using the RNAscope Fluorescent Multiplex Detection v2 kit (ACD) as previously described ( 52 ). The ush2a target probe and odc1 and dapB control probes were designed and provided by ACD.…”
Section: Methodsmentioning
confidence: 99%
“…Cryosections were prepared from adult enucleated eyes or whole larvae and immunostained as previously described ( 10 , 52 ). Primary antibodies used were 4D2 (1:200; Abcam, Cambridge, UK; ab98887), anti-UV opsin, anti-blue opsin, anti-red opsin (1:200; gifted by Professor David Hyde, University of Notre Dame), anti-usherin-C (1:500; Novus Biological, Littleton, CO, USA; 27 640 002), anti-usherin-N (1:200; gifted by Dr Jennifer Phillips, University of Oregon), anti-LC3 (1:200; Thermo Fisher Scientific, Waltham, MA, USA; PA1-16930), anti-centrin (1:500; Merck-Millipore; 04-1624) or anti-acetylated tubulin (1:200; Sigma-Aldrich, St Louis, MO, USA; T7451).…”
Section: Methodsmentioning
confidence: 99%
“…61 Since the energy demands of the cell dictates the mitochondrion count, RPE cells have an enriched mitochondrial population to meet the energy demands of the outer retina. 62 Early studies treating RPE cells with H 2 O 2 to induce oxidative stress showed preferential damage of mitochondrial DNA and subsequently provided a rationale for a model of AMD that is mitochondrion-based. 63 Recently, there is increasing evidence of an age-related decline in mitochondrial function in people with AMD.…”
Section: Dysfunctional Mitochondriamentioning
confidence: 99%
“…RPE also metabolizes fatty acids to produce b‐hydroxybutarate, which can be used as an alternate energy source 61 . Since the energy demands of the cell dictates the mitochondrion count, RPE cells have an enriched mitochondrial population to meet the energy demands of the outer retina 62 …”
Section: Dysfunctional Mitochondriamentioning
confidence: 99%
“…So it was controversial whether autophagy played protective or harmful effects. Defects in phagosome was related to a variety of cellular metabolic process, including abnormal lipid metabolism, oxidative stress injure and mitochondrial dysfunction [31][32][33] but autophagosome accumulation could impair cell bioenergetics and also induce cell death 34 . We proposed that the response to autophagosome varied widely, depending on the severity of mitochondrial de ciency.…”
Section: Melasmentioning
confidence: 99%